THE INFLUENCE OF MOTIVATION, LEARNING STYLES, TEACHER LEADERSHIP, AND TEACHING INTENSITY ON STUDENTS’ LEANING OUTCOMES - Sulistiyarini, Dewi; Sukardi, Sukardi (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study aims to determine the correlation and the contribution of motivation, learning styles, teacher leadership, and the intensity of teaching on the learning outcomes of X grade students in Mathematics at Vocational High Schools. This study is an ex-post facto with a total sample of 234 students. The data is collected by questionnaire and analyzed by descriptive statistics as well as correlation and multiple regression with significance level of 5%. The analysis shows that the students’ motivation and learning styles still need to be improved, while the teacher leadership and teaching intensity need to be maintained. The result of correlation analysis shows that motivation, learning styles, teachers’ leadership, teaching intensity, and learning outcomes correlate from 0.532 to 0.627. The result of dual regression analysis shows that the contribution of motivation learning styles, teachers’ leadership and teaching intensity on the students’ learning outcomes were 0.381, 0,199, 0.223 and 0.175 respectively.